Nanoscale pores introduced into paper via mesoporous silica coatings using sol-gel chemistry - Mikolei, J. J. (2023)
Mesopores, with diameters between 2 and 50 nm, not only increase the specific surface area, but also generate hierarchically porous materials with specific properties such as capillary fluid transport, ion specific pore accessibility, or size exclusion. Paper is a strongly hierarchical, porous material with specific properties, such as capillary force-driven fluid transport. However, paper fibers change their morphology during the initial step of wood disintegration. This results in changes of the porous fiber structure. In particular paper fibers loose their mesopores during the final drying step in the fabrication process. Here, we investigate silica mesopore formation in paper by sol-gel chemistry and evaporation induced self-assembly to specifically introduce and rationally design mesopore formation and distribution in cotton linter and eucalyptus sulfate paper sheets. We demonstrate the importance of synchronizing the solvent evaporation rate and capillary fluid velocity to ensure mesopore formation as well as the influence of the fiber type and sol-gel solution composition. The combination of argon and krypton sorption, SAXS, TEM and CLSM provides systematic analysis of the porous structure and the silica distribution along the cellulose paper fiber length and cross-section. These results provide a deeper understanding of mesopore formation in paper and how the latter is influenced by paper fluidic properties.